Dalit Studies - Rawat, Ramnarayan S. (Duke University Press, 2016)
The academic field of Dalit studies is relatively new, emerging since the 1990s in South Asia and in diasporic communities. Dalit intellectuals theorize Indian historiography and social sciences through the lenses of humiliation and dignity, pointing to the painful history of Dalit groups (formerly called untouchables) and the contemporary perpetuation of caste inequality. As part of a challenge to high-caste Hindu intelligentsia with privileged upbringings, DALIT STUDIES includes a high proportion of Dalit scholars from non-elite social and institutional backgrounds. Contributors analyze the work of Dalit activists across colonial and postcolonial periods, countering a tradition of viewing them as passive victims and objects of reform. This title was made Open Access by libraries from around the world through Knowledge Unlatched.